The role of the educational supervisor in improving the teaching performance of Islamic studies teachers to raise the academic achievement of middle school students - Al-Shehri, Hanan Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the role of the educational supervisor in improving the teaching performance of teachers of Islamic studies in order to raise the academic achievement of middle school students. It used the descriptive analytical approach and the questionnaire as a tool. The educational supervisor in improving the teaching performance of Islamic studies teachers to raise the academic achievement of middle school students came to a large degree, with a support rate of 69.63%. The study also showed that the highest role of the educational supervisor in improving the teaching performance of teachers of Islamic studies to raise academic achievement is "planning to provide an educational environment that stimulates raising academic achievement", with a support rate of 70.88%. The study showed that the least role of the educational supervisor in improving the teaching performance of teachers of Islamic studies to raise academic achievement was in “preparing evaluation tools that raise academic achievement”, with a support rate of 68.69%. The intermediate stage in Islamic studies from the point of view of the teachers of the subject came to a large degree, with a support rate of 69.31%. Based on the results of the study, one of its most important recommendations was: Preparing a plan to increase the role of the educational supervisor in improving the teaching performance of teachers to raise academic achievement in Islamic studies.
Keywords: educational supervision; performance improvement; teaching; academic achievement; Islamic studies course